A window on the deep ocean: The special value of ocean bottom pressure for monitoring the large-scale, deep-ocean circulation. (February 2018) - Hughes, Chris W.; Williams, Joanne; Blaker, Adam; Coward, Andrew; Stepanov, Vladimir
Highlights: Measuring ocean bottom pressure offers an efficient means to monitor ocean climate. Ocean eddies are strongly suppressed by the continental slope. Deep ocean boundary pressure changes are coherent over more than 10, 000 km. Abstract: We show how, by focusing on bottom pressure measurements particularly on the global continental slope, it is possible to avoid the "fog" of mesoscale variability which dominates most observables in the deep ocean. This makes it possible to monitor those aspects of the ocean circulation which are most important for global scale ocean variability and climate. We therefore argue that such measurements should be considered an important future component of the Global Ocean Observing System, to complement the present open-ocean and coastal elements. Our conclusions are founded on both theoretical arguments, and diagnostics from a fine-resolution ocean model that has realistic amplitudes and spectra of mesoscale variability. These show that boundary pressure variations are coherent over along-slope distances of tens of thousands of kilometres, for several vertical modes. We illustrate the value of this in the model Atlantic, by determining the time for boundary and equatorial waves to complete a circuit of the northern basin (115 and 205 days for the first and second vertical modes), showing how the boundary features compare with basin-scale theoretical models, and demonstrating the ability to monitor the meridional overturning circulation using these boundary measurements. Finally, we discuss applicability to the real ocean and make recommendations on how to make such measurements without contamination from instrumental drift.